Factors associated with child removal among American Indian and Alaska native people in an alcohol intervention study - Lyons, Abram J. (Child maltreatment, 2023)
This study was a secondary data analysis of factors associated with alcohol-related child removal among American Indian/Alaska Native (AI/AN) adults enrolled in a clinical trial of an alcohol intervention. Among 326 parent participants, 40% reported ever having a child removed from their care in part because of the parent’s alcohol use, defined here as alcohol-related child removal. Seventy-five percent of parents reported at least one separation during their own childhood (M = 1.3, SD = 1.0). In a multivariable analysis, alcohol-related child removal was associated with parental boarding school attendance. No relationship was found between alcohol-related child removal and alcohol intervention outcomes. Results may provide evidence of multigenerational child removal impacts of boarding schools on AI/AN adults receiving an alcohol use disorder intervention. Assessment of parental history of child removal by practitioners, strategies to prevent alcohol-related separation and to support reunification should be integrated into addiction treatment in AI/AN communities.